PENGARUH KOMITMEN ORGANISASI TERHADAP PERILAKU KEWARGANEGARAAN ORGANISASI PADA KARYAWAN PT. BINATAMA AKRINDO JAKARTA - Gendis tirtha marsidini; Irma Rosalinda (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2014)
Abstract The study was conducted to determine the effect of organizational commitment with organizational citizenship behavior to employees. The population in this study were employees at all division of PT. Binata Akrindo. Samples used in this study amounted 34 employees. Sampling using a purposive sampling technique. The Study make use of two instruments as a measure of organizational commitment and organizational citizenship behavior with Likert models. Processing method of data analysis techniques in the testing hypothesis using Regression Analysis. The hypothesis in this study that there is significant influence between organizational commitment and organizational citizenship behavior in employees. The study explains that there is significant influence between organizational commitment with organizational citizenship behavior in employees of PT. Binatama Akrindo Jakarta. Regression equation obtained is Y = 32.894 + 0.450 X, which means there is a positive influence between organizational commitmen with organizational citizenship behavior with the value F = 141.062; p = 0.000 < 0.05 (significant). The amount of influence (R Square) to the occurence of organizational commitment and organizational citizenship behavior is 0.815 (81.5%) which means that the organizational commitment affects organizational citizenship behavior by 81.5% and the remaining influenced by other factors outside of organizational commitment.It can be interpreted any significant positive effect of organizational commitment and the occurrence of organizational citizenship behavior. The study concluded that the higher score on organizational commitment, have the higher also the occurrence of organizational citizeship behavior in employees and if a employees has a lower score on organizational commitment it will also lower the occurrence of organizational citizenship behavior. Key words: organizational commitment, organizational citizenship behavior